Asporogenous Bacillus thuringiensis Mutant Producing High Yields of δ-Endotoxin - Wakisaka, Yoshiharu (1982)
An asporogenous Bacillus thuringiensis subsp. kurstaki strain IK mutant, strain 290-1, which produced high yields of δ-endotoxin, was obtained by ethyl methane sulfonate treatment of a spore suspension. The mutant strain produced about the same amount of δ-endotoxin as that produced by the parent strain, but 10(10) to 10(11) cells did not form any detectable dormant spores.